Colostrum avoidance practice among primipara mothers in urban Northwest Ethiopia. A cross-sectional study - Tilksew Ayalew; Eden Asmare (BMC, 2021)
Abstract Background Breast milk is the ideal and complete form of nutrition for infants colostrum contains all the necessary nutrients for infants' growth and development and antibodies that can protect from many childhood illnesses. Understanding the extent of and barriers to colostrum avoidance in Ethiopia is important for learning how to best improve optimal breastfeeding. No single study has been conducted on primigavida mothers in the country. Therefore, this study aimed to assess the rate of colostrum avoidance practice and associated factors among primigavida mothers. Method A community- based cross-sectional study was conducted from March to April 2016 among (n = 398) randomly selected primigavida mothers in Bahir Dar city, northwest Ethiopia. Data were collected using a structured interviewer-administered questionnaire and analyzed using SPSS version25. Bivariate and multivariate logistic regression analyses were carried out. Odds ratio with 95% confidence interval was used to measure the strength of association. Statistical significance was declared at P-value ≤0.05. Results Out of 398 primipara mothers, 8.8% discarded colostrum. The most common reasons for discarding colostrum were; yellow and creamy (39.2%), bad for infant (35.2%), traditional/cultural reason (17.1%) and infant unable to feed (8.5%). Married mothers (AOR = 4.52, 95%CI: 1.13, 18.16), unemployed mothers (AOR = 3.46, 95%CI: 1.15, 10.51), mothers underwent normal delivery (AOR = 5.20, 95%CI: 1.87, 20.90) and mothers who initiated breastfeeding within 1 h (AOR = 2.79, 95%CI: 0.96, 8.16) were less likely to discard colostrum. Conclusion The current study revealed that colostrum was discarded by 8.8% of primipara mothers. Primipara mothers who were married, unemployed, underwent normal delivery and initiated breastfeeding within 1 h were less likely to discard colostrum. These results suggest that multi-sectorial and multi-disciplinary approaches are needed to decrease colostrum avoidance among primipara mothers in Ethiopia.